The Effects of Self-Efficacy Promotion Programs for Disease Prevention Based on the 3S.3E.1R. Principle with Digital Health Media Monitoring on Health Information of Pre-Diabetes and Pre-Hypertension Group - Rujirapong, Sutthinee (Journal of Phrae Public Health for Development - วารสารสาธารณสุขแพร่เพื่อการพัฒนา, 2025)
This quasi-experimental research aimed to examine the effects of a self-efficacy promotion program for disease prevention based on the 3S.3E.1R. principle combined with digital health media follow-up on health status of individuals at risk or suspected of having diabetes mellitus and hypertension. The participants consisted of 52 individuals living in Den Chai District, Phrae Province. The intervention and follow-up period lasted for 12 weeks. The research instruments included: (1) a self-efficacy promotion program for disease prevention based on the 3S.3E.1R. principle combined with digital health media follow-up, (2) a personal information record form, (3) a knowledge assessment questionnaire on diabetes mellitus and hypertension, (4) a disease prevention behavior questionnaire, (5) a self-efficacy perception questionnaire for disease prevention, and (6) a health record form. The reliability coefficients of the instruments ranged from 0.75 to 0.89. Data were analyzed using descriptive statistics, Fisher’s exact test, and t-tests. The results revealed that after the intervention, the experimental group demonstrated significantly higher mean scores of knowledge regarding diabetes mellitus and hypertension, disease prevention behaviors, and self-efficacy perception compared to the pre-intervention period (p < 0.05). Additionally, the mean body mass index, waist circumference, blood glucose levels, systolic blood pressure, and diastolic blood pressure significantly decreased after the intervention (p < 0.05). These outcomes were also significantly different from those of the control group at the 0.05 level.